Odpowiedzi

2010-03-11T18:09:48+01:00
A)-3x=2x-10
-3x-2x=-10
-5x=-10/:-5
x=2
b)2x-2=7-x
2x+x=7+2
3x=9/:3
x=3
c)10=4-2x
10-4=-2x
6=-2x/:-2
x=-3
d)-(2x-1)=4
-2x+1=4
-2x=4-1
-2x=3/:-2
x= -1 i 1/2

e)2(x+1)=x
2x+2 = x
x=-2

f)2t-(3t+1)=6
2t-3t-1=6
-t=6+1
t=-7

g)-(4+x)=2(3-x)
-4-x=6-2x
-x+2x=6+4
x=10
h)3(y+6)-y=2(y+9)
3y+18-y=2y+18
3y-y-2y=18-18
0=0
i)(x-7)-2(3x+5)=3
x-7-6x-10=3
-5x=3+10+7
-5x=20 /: -5
x= -4
2010-03-11T18:16:04+01:00
A)
-3x=2x-10/-2x
-5x=-10/:(-5)
x=2


b)
2x-2=7-x/+x
3x-2=7/+2
3x=9/:3
x=3


c)
10=4-2x/-4
6=-2x/:(-2)
-3=x


d)
-(2x-1)=4
-2x+1=4/-1
-2x=3/:(-2)
x=-2/3


e)
2(x+1)=x
2x+2=x/-2x
2=-x
x=-2


f)
2t-(3t+1)=6
2t-3t-1=6/+1
-t=7
t=-7


g)
-(4+x)=2(3-x)
-4-x=6-2x/+4
-x=10-2x/+2x
x=10


h)
3(y+6)-y=2(y+9)
3y+18-y=2y+18/-18
2y=2y
0=0
nie można


i)
(x-7)-2(3x+5)=3
x-7-6x-10=3/+17
-5x=20/:(-5)
x=-4
Najlepsza Odpowiedź!
2010-03-11T18:19:28+01:00
A)
-3x=2x-10
-3x-2x=-10
-5x=-10/:(-5)
x=2
b)2x-2=7-x
2x+x=7+2
3x=9/:3
x=3
c)
10=4-2x
2x=4-10
2x=-6:2
x=-3
d)
-(2x-1)=4
-2x+1=4
-2x=4-1
-2x=3:(-2)
x=-3/2
x=-1,5
e)
2(x+1)=x
2x+2=x
2x-x=-2
x=-2
f)
2t-(3t+1)=6
2t-3t-1=6
-t=6+1
-t=7:(-1)
t=-7
g)
-(4+x)=2(3-x)
-4-x=6-2x
-x+2x=6+4
x=10
h)
3(y+6)-y=2(y+9)
3y+18-y=2y+18
2y-2y=18-18
0=0
i)
(x-7)-2(3x+5)=3
x-7-6x-10=3
-5x=3+7+10
-5x=20:(-5)
x=-4